Catholic Church, education and laicity in Argentinean history - Torres, German Santos Maria (2014)
The aim of this paper is to analyze, in a historical perspective, the relationship between Catholic Church and the field of public education in Argentina, taking laicity as a conceptual axis. We assume that the different configurations of the relationship between Church and State can be defined following the tensions over education governance. We present a periodization, ranging from the colonial period to the beginning of the 21st century, through which we identify lines of continuity, tensions and re-articulations of educational laicity as well as strategies of the Church, the State and civil society actors in different historical moments.